Developing a Collective Awareness Platform for Urban Sustainability Challenges: Case Study of the POWER Project - Ksenia Koroleva, Mathias Becker; Diogo Vitorino, Kalina Drenska; Novak, Jasminko (European Journal of Sustainable Development, 2019)
In this paper we describe the socio-technical approach developed in the POWER project extending traditional forms of citizen engagement for local sustainability challenges with a collective awareness platform in order to increase public awareness, knowledge and engagement. We show how a citizen-centered design and implementation process integrating different technological enablers such as gamification, real-time open data integration or knowledge visualization results in a platform for sustainability issues that can drive collective awareness and collaborative knowledge sharing. Against the background of four different pilot cities with distinct water-related sustainability challenges, we present the implementation of the local platforms and how these have been effectively used by almost 1.000 active users, supporting an innovative engagement model that employed collaborative open innovation in online and offline settings for citizen-driven solution development to local sustainability challenges. We present the results from three series of citizen workshops where 150 participants provided valuable feedback, which was integrated in the further platform improvement. The evaluation confirmed its usability, enabling platform uptake among the target groups and its social impact by increasing awareness and knowledge. Finally, we derive a set of implications for similar initiatives addressing sustainability challenges helping them to overcome common barriers to participation and engagement. Keywords: citizen engagement, digital citizenship, sustainable urbanism, education, governance sustainability, gamification, water conservation, disaster risk reduction